A Study on Entrepreneurial Schemes of NBCFDC - Suman, Tanuja (International Journal of Engineering and Management Research, 2025)
The National Backward Classes Finance and Development Corporation (NBCFDC) plays a pivotal role in promoting the economic empowerment of backward classes in India through various enterprise development programs. Established under the Ministry of Social Justice and Empowerment, NBCFDC provides financial support, skill development, and other resources to foster entrepreneurship among economically disadvantaged communities. The corporation offers a range of financial products, including loans, subsidies, and venture capital funds, aimed at improving the economic conditions of backward classes. This paper explores NBCFDC’s mission, the types of entrepreneurial schemes it supports, and its impact on the socio-economic development of backward classes. With a focus on providing access to financial resources and skill training, NBCFDC helps individuals and communities achieve financial independence and long-term sustainability through entrepreneurship.